Mature dendritic cells prime functionally superior melan-A-specific CD8+ lymphocytes as compared with nonprofessional APC. - Salio, M; Shepherd, D; Dunbar, P; Palmowski, M; Murphy, K; Wu, L; Cerundolo, V (2001)
Priming of melan-A(26/27-35)-specific CTL occurs only in a fraction of late stage melanoma patients, whereas during the early stages of the disease and in healthy volunteers, melan-A CTL have functional and phenotypic markers consistent with a naive phenotype. To study the requirements for expansion of naive melan-A CTL from healthy donors, we set up an in vitro priming protocol and, using tetramer assays, we demonstrate that the activity and phenotype of the expanded melan-A CTL are profoundly influenced by the type of APC used. Priming by nonprofessional APC leads to expansion of melan-A CTL with reduced cytolytic activity and low level of IFN-gamma secretion. In contrast, mature dendritic cells (DC) expand cytolytic and IFN-gamma-producing melan-A CTL. Priming by mature DC is also efficient at low peptide concentration and requires only one round of stimulation. Finally, we observed that a significant fraction of CD45RO(+) melan-A CTL primed by mature DC expresses high levels of the homing receptor CD62L, whereas CTL primed by nonprofessional APC express CD62L in lower percentages and at lower levels. These results suggest that suboptimal priming by nonprofessional APC could account for the presence in vivo of dysfunctional cells and strongly support the immunotherapeutic use of mature DC for expansion of effector and memory Ag-specific CTL.